Mitigation of aflatoxin contamination of maize, groundnut, and sorghum by commercial biocontrol products in farmers’ fields across Burkina Faso, Mali, Niger, and Togo - Bonkoungou, S.; Dagno, K.; Basso, A.; Ekanao, T.; Atehnkeng, J.; Agbetiameh, D.; Neya, A.; Toure, M.; Tiendrebeogo, A.; Konate, M.; Outani, B.; Konlambigue, M.; et al. (CAB International, 2024)
Background Aflatoxin contamination by Aspergillus section Flavi fungi poses a significant threat to food security and public health in sub-Saharan Africa (SSA). Maize, groundnut, and sorghum are staple crops frequently contaminated with aflatoxins, sometimes at dangerous levels. Despite its detrimental effects, many farmers in SSA lack access to effective tools for mitigating aflatoxin contamination. Biocontrol based on atoxigenic isolates of A. flavus is an effective tool to limit aflatoxin contamination.